Phylogenetic relationships and morphological variation of gymnures (Galericidae: Hylomys) from Genting Highlands, Pahang, Malaysia - Muhammad Farhan Abd Wahab; Motokawa, Masaharu; Faisal Ali Anwarali Khan; Dharini Pathmanathan; Hasmahzaiti Omar (Penerbit Universiti Kebangsaan Malaysia, 2022)
Gymnures from the genus Hylomys are widely distributed across Sundaland and the Indochinese region. However, the relationships among its members in Peninsular Malaysia especially from Genting Highlands are still lacking. This study aims to examine the morphology and genetically analyse of the Hylomys specimens collected from the new isolated population of Genting Highlands, Pahang, Malaysia. Morphometric analyses showed that morphological variation exists among the Hylomys lineage. The external morphology and the skull measurements of the taxa studied coincide with those of Hylomys maxi from Peninsular Malaysia and Sumatra based on descriptive statistics and principal component analysis (PCA). The differences within the Hylomys taxa are also evident in the phylogenetic tree and K2P genetic distances analyses inferred from cyt b. Hylomys samples from Genting Highlands formed a clade with H. maxi from Cameron Highlands and Fraser’s Hill, Peninsular Malaysia and Sumatra. However, they were separated from Hylomys parvus (Sumatra), Hylomys suillus (Java) and Hylomys dorsalis (Borneo). Relatively, low genetic distances were detected among the studied taxa with other H. maxi (<6% K2P distance) while high genetic distances were observed when compared to other Hylomys taxa (>18.0% K2P distance). Based on these facts, we confirm that the gymnures from Genting Highlands belong to a valid species, Hylomys maxi along with other Peninsular Malaysia samples based on genetics and morphological data which probably originated from Sumatra a long time ago.